Impact of Marital Status on Prognosis of Patients With Invasive Breast Cancer: A Population-Based Study Using SEER Database - Jiao, Dechuang; Ma, Youzhao; Zhu, Jiujun; Dai, Hao; Yang, Yue; Zhao, Yajie; Guo, Xuhui; Liu, Zhenzhen (Frontiers in Oncology, 2022)
Objective: This study aimed to investigate the prognostic roles of marital status in patients with invasive breast cancer. Method: We extracted the data of patients with invasive breast cancer who were diagnosed during 2010–2015 and had complete staging and molecular typing from the Surveillance, Epidemiology, and End Results (SEER)-18 database. Kaplan–Meier curve method and Cox regression analysis were performed to investigate the differences in breast cancer–specific survival (BCSS) and overall survival (OS) in the total population and various subgroups with different marital statuses. Results: Among the 324,062 patients with breast cancer in this study, 55.0%, 40.0%, and 5.0% were married, unmarried, and unknown, respectively; 51.8%, 32.2%, 10.5%, and 5.5% were patients with Stages Ⅰ, Ⅱ, Ⅲ, and Ⅳ breast cancer, respectively. The 5-year BCSS and OS of married patients were 92.6% and 88.1%, respectively, higher than those of unmarried patients (88.3% and 78.1%, P < 0.001). After adjustment for sex, age, T and N stages, histological grade, insurance status, race, year of diagnosis, and molecular subtypes, married status was an independent predictor of better BCSS [hazard ratio (HR) = 0.775, 95% confidence interval (CI) = 0.753–0.797, P < 0.001) and OS (HR = 0.667, 95% CI = 0.653–0.681, P < 0.001). After multivariate analysis of various subgroups of sex, age, stage, histological grade, insurance status, race, and molecular subtype, married status was an independent predictor of better BCSS in all subgroups except for Grade Ⅳ, age < 35 years, and uninsured subgroups. Marital status was an independent predictor of better OS in all subgroups except the subgroup with age <35 years. Conclusions: In conclusion, marital status was an independent prognostic factor for breast cancer. The unmarried patients with breast cancer had a worse prognosis, except for the subgroup with age <35 years. Hence, unmarried patients with breast cancer and age ≥35 years may need additional psychosocial and emotional support to achieve more prolonged survival, besides active treatment of primary disease.